Dissociation of methane and carbon dioxide hydrates: Synergistic effects; Fuel; Vol. 359 - Gaydukova O. S. Olga Sergeevna; Dorokhov V. V. Vadim Valerjevich; Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen